2001
DOI: 10.1002/micr.1050
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐channel orbicularis oculi stimulation to restore eye‐blink function in facial paralysis

Abstract: Facial paralysis due to facial nerve injury results in the loss of function of the muscles of the hemiface. The most serious complication in extreme cases is the loss of vision. In this study, we compared the effectiveness of single- and multiple-channel electrical stimulation to restore a complete and cosmetically acceptable eye blink. We established bilateral orbicularis oculi muscle (OOM) paralysis in eight dogs; the OOM of one side was directly stimulated using single-channel electrical stimulation and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 66 publications
(38 reference statements)
0
25
0
Order By: Relevance
“…A prior study observed that rabbits initially flinched in response to orbicularis oculi stimulation, but signs of pain diminished over time (Otto, 1997). There is evidence that FES paradigms including interferential stimulation (McDonnall et al, 2009) and low-intensity multichannel stimulation (Somia et al, 2001) render facial muscle stimulation functional but not painful. Finally, facial FES has been achieved in humans reporting only mild pain (McDonnall et al, 2009; Frigerio et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prior study observed that rabbits initially flinched in response to orbicularis oculi stimulation, but signs of pain diminished over time (Otto, 1997). There is evidence that FES paradigms including interferential stimulation (McDonnall et al, 2009) and low-intensity multichannel stimulation (Somia et al, 2001) render facial muscle stimulation functional but not painful. Finally, facial FES has been achieved in humans reporting only mild pain (McDonnall et al, 2009; Frigerio et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of FES in activating paralyzed facial muscles, in particular the orbicularis oculi to restore eye blink, has been demonstrated in rabbits and dogs (Rothstein and Berlinger, 1986; Salerno et al, 1991; Otto, 1997; Somia et al, 2001; Sachs et al, 2007; Jie et al, 2016). Since many facial movements including eye blink are symmetric, a natural closed-loop FES control signal in unilateral facial paralysis can be derived from the intact side of the face.…”
Section: Introductionmentioning
confidence: 99%
“…Good results have also been reported in working with spinal injuries [14][15][16], facial nerve paralysis [17], and quadriplegia [2], as well as in the treatment of conditions such as child epilepsy [18][19] and Parkinson's disease [20]. Further, while not yet formally reported in academic papers, attempts are also being made to use stimulating electrode implants to achieve lasting recovery in cases of nerve damage.…”
Section: Application To Medical Treatmentmentioning
confidence: 99%
“…Biological tissues and body fluids also respond to electrode electrolysis, corrosion and electrical characteristics in different ways. 5,6 These differences must be controlled within a certain range to guarantee proper function of the implanted materials in the facial nerve system and prevent harm to biological tissue. Implant studies are critical for clarifying and addressing these effects and differences.…”
Section: Introductionmentioning
confidence: 99%